Recombinant Human Erythropoietin Increases Blood Pressure, Platelet Aggregability and Platelet Free Calcium Mobilisation in Uraemic Children: A Possible Link? - Van Geet, Chris; Damme-Lombaerts, Rita Van; Vanrusselt, Marleen; MOl, An de; Proesmans, Willy; Vermylen, Jos (Thrombosis and Haemostasis, 1990)
Recombinant human erythropoietin was administered to 10 uraemic children on chronic haemodialysis, all of whom responded by correcting their haemoglobin. In addition, they showed an increase in blood pressure; platelet aggregations, subnormal before therapy, improved during treatment. The intracellular free calcium concentration in platelets after thrombin stimulation also increased significantly during erythropoietin administration. We hypothesize that the effect of erythropoietin on platelet aggregability and on blood pressure may be due to an increase in the intracellular free calcium mobilisation in platelets and possibly in smooth muscle cells respectively.